THE EVOLUTION OF WEB DEVELOPMENT: FROM STATIC PAGES TO DYNAMIC WEB APPLICATIONS (International journal of artificial intelligence, 2025)
Web development has undergone a remarkable transformation over the past few decades, evolving from simple static web pages to complex, dynamic web applications. Initially, websites were static, consisting of HTML pages that displayed fixed content, offering limited interaction with users. However, with the advent of dynamic technologies such as JavaScript, CSS, and server-side scripting languages, web development has shifted towards creating interactive and responsive web applications that offer real-time user engagement, personalized experiences, and seamless functionality across devices. This article explores the journey of web development, examining key milestones such as the rise of JavaScript frameworks, the importance of responsive design, and the emergence of modern web development practices like Single Page Applications (SPAs), Progressive Web Apps (PWAs), and the use of APIs to connect with external services. The article will also discuss the future trends shaping web development, including the growing use of artificial intelligence, the shift to serverless computing, and the integration of Web 3.0 technologies.